A metal–organic framework/polymer derived catalyst containing single-atom nickel species for electrocatalysis. Issue 40 (8th October 2020) - Yang, Shuliang; Zhang, Jie; Peng, Li; Asgari, Mehrdad; Stoian, Dragos; Kochetygov, Ilia; Luo, Wen; Oveisi, Emad; Trukhina, Olga; Clark, Adam H.; Sun, Daniel T.; Queen, Wendy L.
Abstract : A metal–organic framework/polymer derived catalyst containing single-atom nickel species shows good performance for electroreduction of CO2 to CO. Abstract : While metal–organic frameworks (MOF) alone offer a wide range of structural tunability, the formation of composites, through the introduction of other non-native species, like polymers, can further broaden their structure/property spectrum. Here we demonstrate that a polymer, placed inside the MOF pores, can support the collapsible MOF and help inhibit the aggregation of nickel during pyrolysis; this leads to the formation of single atom nickel species in the resulting nitrogen doped carbons, and dramatically improves the activity, CO selectivity and stability in electrochemical CO2 reduction reaction. Considering the vast number of multifarious MOFs and polymers to choose from, we believe this strategy can open up more possibilities in the field of catalyst design, and further contribute to the already expansive set of MOF applications.